Effect of pyrethroid insecticides on the photosynthetic activity of pea mesophyll protoplasts - Rózsavölgyi, Tamás; Horváth, Ferenc (Acta Biologica Szegediensis, 2008)
Pyrethroids are plant protecting substances whose effects on treated plants are widely monitored with often conflicting results. Field experiments showed no alteration in photosynthetic rates by a synthetic pyrethroid permethrin (Haile et al. 1999), while other studies showed an inhibition in PSII reactions by the halogen side of the molecules, and suggested QA as a target site of interaction, like in the case of urea-type herbicides (Bader and Schuler 1996). In order to clarify these opposing observations, photosynthetic effects of pyrethroids were re-tested.